On-Farm Verification of Linseed and Sesame Variety for Fallow-Fallow-T Aman Rice Cropping System in Sylhet Region of Bangladesh (Bangladesh Agronomy Journal, 2017)
A field experiment was conducted during rabi and kharif seasons of 2014-15 and 2015-16 to find out suitable linseed and sesame genotypes to fit in the Fallow-Fallow- T. aman rice cropping system under AEZ 20 in Sylhet region of Bangladesh. This experiment was laid out in a randomized complete block design (RCBD) with six dispersed replications. It was revealed that among the different linseed varieties, the genotype Zokiganj-local gave the maximum number (31.40) of capsules plant-1 and 1000-seed weight (4.01g) with the highest seed yield (1003 kg ha-1). Similarly, sesame var. BARI Til-4 provided maximum number of capsules plant-1 (71.33), seeds plant-1 (70.33) and highest 1000-seed weight (3.012g), which resulted the highest seed yield (1150 kg ha-1) yield in arable fallow land of Sylhet region. The lowest seed yield 782 and 840 kg ha-1 of linseed and sesame was produced by the genotypes Patuakhali local and the var. BARI Til-3, respectively.Bangladesh Agron. J. 2017, 20(1): 7-12